2020
DOI: 10.1155/2020/7301615
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Effect of Hydrogen Sulfide and Its Role in Traumatic Brain Injury

Abstract: Ever since endogenous hydrogen sulfide (H2S) was found in mammals in 1989, accumulated evidence has demonstrated that H2S functions as a novel neurological gasotransmitter in brain tissues and may play a key role in traumatic brain injury. It has been proved that H2S has an antioxidant, anti-inflammatory, and antiapoptosis function in the neuron system and functions as a neuroprotective factor against secondary brain injury. In addition, H2S has other biologic effects such as regulating the intracellular conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…H 2 S has been described as a potent antioxidant in several organ systems [ 48 , 49 , 50 ]. In a murine model of acute lung injury induced by LPS-induced endotoxemia, the H 2 S donor GYY 4137 attenuated the LPS-induced decrease in the antioxidative biomarkers catalase and SOD and the total antioxidant capacity (T-AOC) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S has been described as a potent antioxidant in several organ systems [ 48 , 49 , 50 ]. In a murine model of acute lung injury induced by LPS-induced endotoxemia, the H 2 S donor GYY 4137 attenuated the LPS-induced decrease in the antioxidative biomarkers catalase and SOD and the total antioxidant capacity (T-AOC) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S can bind to hemoglobin to form sulfhemoglobin, which may be one of the storage forms of H 2 S in vivo 30 . In addition, the recognized form of H 2 S storage in the body is the acid‐labile sulfur pool such as iron‐sulfur cluster‐containing proteins, and reductant‐labile sulfane sulfur pool, which include hydrodisulfides/persulfides 45,46 …”
Section: Storage Of H2smentioning
confidence: 99%
“…30 In addition, the recognized form of H 2 S storage in the body is the acid-labile sulfur pool such as iron-sulfur cluster-containing proteins, and reductant-labile sulfane sulfur pool, which include hydrodisulfides/persulfides. 45,46…”
Section: S Tor Ag E Of H 2 Smentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen sulfide (H 2 S) is a gaseous neurotransmitter that has been synthesized endogenously by cystathionine-γ-lyase and cystathionine-β-synthase 13 . Studies have shown the function of physiological and pathophysiological roles of H 2 S in the brain including traumatic brain injury 14 , 15 . Furthermore, other studies have pointed out the close interrelationship between H 2 S, neuroinflammation and Nrf2 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%